ANALISIS KONTEN KUALITATIF HOAKS DAN LITERASI DIGITAL DALAM @KOMIKFUNDAY - Monggilo, Zainuddin Muda Z (Interaksi: Jurnal Ilmu Komunikasi, 2020)
This research uses a qualitative approach with qualitative content analysis as a method to describe the hoaxes and the meaning of digital literacy competencies that are visualized in a comic strip distributed through an Instagram account @komikfunday. A total of 25 comic strips act as an analysis unit with subunits containing textual and non-textual comic elements from each comic strip panel. Qualitative interpretation of the content is divided into two levels namely the explicit meaning and the implicit meaning. Digital literacy competencies are adapted from the ten competencies developed by the Indonesian Digital Literacy Advocacy Networks (Japelidi). The result shows that the explicit meaning of each content is a mission to eradicate hoaxes along with tips and strategies that apply to all people. Also, the implicit meaning that is related to digital literacy competencies consists of six competencies called selecting, understanding, analyzing, verifying, evaluating and distributing. Overall, it can be interpreted that @komikfunday has fully integrated the competencies needed by each individual as a provision to fight hoaxes. Thus, it is expected to be present to encourage creative, innovative and collaborative movements in increasing the digital literacy competencies of the Indonesian people massively and evenly.